Nivolumab Induced Lethal Aplastic Anemia in a Patient with Metastatic Melanoma - Keren Rouvinov; Karen Nalbandyan; Victor Kozlov; Nir Peled; Alexander Yakobson (Case Reports in Oncology, 2019)
Nivolumab is an active treatment in patients with metastatic melanoma. We report a case of a patient with metastatic malignant melanoma who was given nivolumab as an advanced-line treatment. She received nivolumab 3 mg/kg every 2 weeks for 4 cycles and developed aplastic anemia. To the best of our knowledge, there are only three published case reports that have shown aplastic anemia in patients who have been treated by immunotherapy. This is the first report of a lethal aplastic anemia during nivolumab monotherapy in a metastatic melanoma patient.